Analysis of the Mesoscale Asymmetric Rainbands during the Slow Northward-Moving Period of Typhoon In-Fa (2021) - Shunan Yang; Yixiong Lu; Yi Hu; Boyu Chen; Zhenya Song; Min Chu (Asia-Pacific Journal of Atmospheric Sciences, 2024)
After making landfall, Typhoon In-Fa (2021) moved slowly, resulting in heavy rainfall and flooding across fourteen provinces in China. This extreme precipitation was primarily linked to the evolution of active mesoscale convective systems. This study analyzes the characteristics and causes of mesoscale rainbands during In-Fa’s slow northward-moving period, aiming to identify the key factors that influence the detailed evolution of typhoon rainbands and to enhance typhoon quantitative precipitation forecasting skill. In-Fa’s mesoscale asymmetric rainbands can be categorized into three types: mesoscale spiral rainbands, a convective rainband to the east of In-Fa, and a rainband to the north of In-Fa. Mesoscale low-level jets are a critical factor in the development of mesoscale spiral rainbands. The wind speed gradient near these jets, along with the convergence of wind directions between two jets, fosters low-level convergence and upward motion, triggering the evolution of several mesoscale rainbands. The convective rainband to the east of In-Fa flourishes under conditions of high humidity and energy, displaying distinct diurnal variations. This is due to the strengthening of low-level jets at night, which enhances both dynamic convergence and water vapor availability. The presence of moderate to strong convective available potential energy (600–1500 J kg −1 ), substantial whole-layer water vapor (relative humidity exceeding 90–95%), and a high 0 °C-layer favors the development of efficient warm-cloud convective precipitation, leading to intense hourly rainfall. The rainband to the north of In-Fa is primarily associated with cold air intrusion in the lower troposphere, although the interaction between typhoon and mid-latitude systems has not yet occurred. At the interface between cold and warm air, the colder air to the north side sinks while the warmer air to the south side rises, forming a secondary circulation that supports the development and persistence of precipitation on the north side of the typhoon. These findings offer a conceptual model for accurately predicting precipitation associated with typhoons that move slowly northward after landfall.